Efektivitas Insektida Nabati dari kombinasi Daun Pepaya, Daun Salam, Serai, Daun Putri Malu dan Bawang Putih Terhadap Mortalitas Kutu Beras (Sitophilus oryzae L) - Choirunisa, Khusnul; Setyaningsih, Endang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to utilize natural ingredients such as papaya leaves, bay leaves, lemongrass, mimosa leaves and garlic as environmentally friendly botanical insecticides in reducing the population of rice weevils (Sitophilus oryzae L). The method used is the experimental method and quantitative descriptive research, this study uses a Completely Randomized Design (CRD) pattern consisting of two factors, namely the dose factor and observation time. In this study there were 3 treatments and 2 replications, namely PI.T1, PI.T2 and P1.T3, and the results were obtained in the P1.T1 treatment with an average of 1 tail, PI.T2 with an average of 10 tails and PI.T3 with an average of 2 tails. Based on the observation time factor, the results were significant in the 24-hour treatment. Based on the research conducted, the results obtained were influenced by several factors, namely the dose and humidity factors. Based on the research conducted, it can be concluded that (1) administering a combination of herbal insecticide doses of papaya leaves, bay leaves, lemongrass, mimosa leaves and garlic and exposure time produced the highest results in the 24-hour treatment, (2) apart from the herbal insecticide dose and exposure time, humidity and temperature are also factors that influence rice weevil mortality.